Elevated Myoglobin in Patients With Primary Aldosteronism: A Cross-Sectional Study - Kang, Bing; Peng, Chuan; Wang, Kanran; Song, Ying; Yang, Yi; Ma, Linqiang; Mei, Mei; Hu, Jinbo; Yang, Shumin; Wu, Fei-Fei; Li, Qifu (Frontiers in Endocrinology, 2022)
Objectives: Primary aldosteronism (PA) is characterized by the autonomous excessive production of aldosterone in the adrenal cortex. Aldosterone is associated with damages to heart muscle and skeletal muscle. The purpose of this study was to evaluate serum levels of muscle injury markers and their associated factors in patients with primary aldosteronism. Methods: We retrospectively enrolled subjects with PA and essential hypertension (EH) who had completed testing for serum high sensitivity troponin T (hs-TnT), creatine kinase isoenzyme MB (CK-MB) and myoglobin from the database of the Chongqing Primary Aldosteronism Study (CONPASS). Univariate and multivariate linear regression analyses were performed to analyze the influencing factors of myocardial injury markers. Results: In total, 278 patients with PA and 445 patients with EH were enrolled in this study. Compared with EH patients, serum concentrations of hs-TnT [7.0 (4.0–12.0) vs. 6.0 (3.0–11.0) ng/L; p=0.005] and myoglobin [24.2 (21.0–38.1) vs. 21.8 (21.0–31.9) μg/L; p=0.023] were significantly higher among PA patients, while no significant difference of CK-MB was found between two groups [1.4 (1.0–2.0) vs. 1.3 (0.9–1.9) μg/L; p=0.154]. Univariate linear regression analysis showed that myoglobin was negatively correlated with serum potassium (β=-0.31; p<0.01) and positively correlated with plasma aldosterone concentration (β=0.40; p<0.01) in the PA group, while no significant correlation was found between hs-TnT and biochemical parameters. After adjusting for multiple confounders, myoglobin was negatively correlated with serum potassium (β=-0.15; p<0.05) and positively correlated with plasma aldosterone concentration (β=0.34; p<0.01) in the PA group. Conclusions: The serum level of myoglobin was significantly increased in PA patients, and myoglobin was independently correlated with plasma aldosterone concentration.